Induction of cell cycle arrest and apoptosis in caspase-3 deficient MCF-7 cells by Dillenia suffruticosa root extract via multiple signaling pathways - Foo, Jhi Biau; Saiful Yazan, Latifah; Tor, Yin Sim; Nurdin, Armania; Ismail, Norsharina; Imam, Mustapha Umar; Yeap, Swee Keong; Cheah, Yoke Kqueen; Abdullah, Rasedee; Ismail, Maznah (BioMed Central, 2014)
Background Dillenia suffruticosa root dichloromethane extract (DCM-DS) has been reported to exhibit strong cytotoxicity towards breast cancer cells. The present study was designed to investigate the cell cycle profile, mode of cell death and signalling pathways of DCM-DS-treated human caspase-3 deficient MCF-7 breast cancer cells.